2020
DOI: 10.1007/s13311-020-00870-1
|View full text |Cite
|
Sign up to set email alerts
|

Administration of FK506 from Late Stage of Disease Prolongs Survival of Human Prion-Inoculated Mice

Abstract: Human prion diseases are etiologically categorized into three forms: sporadic, genetic, and infectious. Sporadic Creutzfeldt-Jakob disease (sCJD) is the most common type of human prion disease that manifests as subacute progressive dementia. No effective therapy for sCJD is currently available. Potential therapeutic compounds are frequently tested in rodents infected with mouse-adapted prions that differ from human prions. However, therapeutic effect varies depending on the prion strain, which is one of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Inhibitors of CaN have already been suggested to mitigate neuropathology in models of Alzheimer’s disease, strokes and, importantly, in mouse models of acquired prion disease [ 27 , 28 , 29 , 67 , 68 , 69 , 70 , 71 , 72 ]. In the context of neuropathology, overactivation and/or overexpression of CaN, specifically in astrocytes, has been associated mainly with reactive gliosis and neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitors of CaN have already been suggested to mitigate neuropathology in models of Alzheimer’s disease, strokes and, importantly, in mouse models of acquired prion disease [ 27 , 28 , 29 , 67 , 68 , 69 , 70 , 71 , 72 ]. In the context of neuropathology, overactivation and/or overexpression of CaN, specifically in astrocytes, has been associated mainly with reactive gliosis and neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Over-activation of CaN plays a pivotal role in reactive gliosis and neuroinflammation in Alzheimer’s disease (AD) [ 10 , 11 , 20 , 21 , 22 , 23 , 24 ]. A preclinical alteration of CaN has been reported in the TgPG14 mouse model of inherited prion disease [ 25 , 26 ], and treatment of prion-infected mice with the CaN inhibitor FK506 delays disease onset and promotes PrP degradation [ 27 , 28 , 29 ]. Moreover, PrP expression level influences the incubation period and disease duration in both prion-infected and mutant PrP mice [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stocki et al proposed that FK506 treatment results in a profound reduction in PrP C expression due to a defect in the translocation of PrP C into the endoplasmic reticulum with subsequent degradation by the proteasome [53]. More recently, treatment with FK506 suppressed typical sCJD pathology (gliosis) and significantly prolonged the survival of sCJD-inoculated mice [41].…”
Section: Discussionmentioning
confidence: 99%
“…Stocki et al proposed that FK506 treatment results in a profound reduction in PrP C expression due to a defect in the translocation of PrP C into the endoplasmic reticulum with subsequent degradation by the proteasome[53]. More recently, treatment with FK506 suppressed typical sCJD pathology (gliosis) and significantly prolonged the survival of sCJD-inoculated mice[41]. Finally, FKBP5 DNA methylation decreases along the lifespan; this age-related decrease is not confounded by blood cell type heterogeneity and occurs in purified immune cell subtypes[63].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in mice suggest that such approaches may be beneficial in individuals with a prion infection in the brain, but the wider impacts of long-term administration of immunosuppressive drugs should not be overlooked. One study, for example, has shown how oral treatment with the immunosuppressant FK506 from the onset of the clinical signs was effective in suppressing microglial responses and reducing disease susceptibility in a mouse sCJD model [ 185 ]. Inhibition of microglial proliferation or “priming” may also have efficacy.…”
Section: Cns Prion Diseasementioning
confidence: 99%